Psychometric properties of a test in evidence based practice: the Spanish version of the Fresno test - Jiménez-Villa Josep; Flores-Mateo Gemma; Argimon-Pallàs Josep M; Pujol-Ribera Enriqueta (BMC Medical Education, 2010)
Abstract Background Validated instruments are needed to evaluate the programmatic impact of Evidence Based Practice (EBP) training and to document the competence of individual trainees. This study aimed to translate the Fresno test into Spanish and subsequently validate it, in order to ensure the equivalence of the Spanish version against the original English version. Methods Before and after study performed between October 2007 and June 2008. Three groups of participants: (a) Mentors of family medicine residents (expert group) (n = 56); (b) Family medicine physicians (intermediate experience group) (n = 17); (c) Family medicine residents (novice group) (n = 202); Medical residents attended an EBP course, and two sets of the test were administered before and after the course. The Fresno test is a performance based measure for use in medical education that assesses EBP skills. The outcome measures were: inter-rater and intra-rater reliability, internal consistency, item analyses, construct validity, feasibility of administration, and responsiveness. Results Inter-rater correlations were 0.95 and 0.85 in the pre-test and the post-test respectively. The overall intra-rater reliability was 0.71 and 0.81 in the pre-test and post-test questionnaire, respectively. Cronbach's alpha was 0.88 and 0.77, respectively. 152 residents (75.2%) returned both sets of the questionnaire. The observed effect size for the residents was 1.77 (CI 95%: 1.57-1.95), the standardised response mean was 1.65 (CI 95%:1.47-1.82). Conclusions The Spanish version of the Fresno test is a useful tool in assessing the knowledge and skills of EBP in Spanish-speaking residents of Family Medicine.